Physics Contributions2D to 3D Evaluation of Organs at Risk Doses in Intracavitary Brachytherapy for Cervical Cancer - Inn Tan, Yun; Ai Choo, Bok; Mun Lee, Khai (Journal of Contemporary Brachytherapy, 2010)
Purpose: To compare International Commission on Radiation Units and Measurements (ICRU) bladder and rectum reference points doses with volumetric doses in 3D intracavitary brachytherapy (ICBT) for cervical cancer. Also to compare bladder, rectum and sigmoid (organs at risk, OARs) volume doses with dose constraints recommended by the (GYN) GEC-ESTRO Working Group. Material and methods: A retrospective study was carried out on 10 patients with a total of 55 fractions CT-based high dose rate (HDR) ICBT. ICRU bladder (bICRU) and rectum (rICRU) points were defined according to ICRU Report 38 on the CT images and prospectively kept to less than 80% of prescription dose to Point A during real treatment planning. Post-treatment, outer wall of OARs were contoured and minimum dose to 2cc (D2cc) of the most irradiated part of the OARs was obtained from the dose-volume histogram (DVH). Total dose (external beam radiotherapy plus ICBT) were computed with ICRU point dose and D2cc and compared. Results: The mean ICRU point dose and D2cc volume dose were found to be significantly different for bladder (per fraction: p = 0.000; total dose: p = 0.004) but no differences were found for rectum (per fraction: p = 0.055; total dose: p = 0.090). bICRU point dose underestimated D2cc dose with an average ratio of 1.34 ± 0.34. 3 out of 10 patients, 7 out of 10 patients, and 5 out of 10 patients exceeded the recommended dose constraint for bladder, rectum, and sigmoid, respectively. Conclusions: bICRU was not representative of bladder D2cc and resulted in different total dose. rICRU was found to be similar to D2cc dose and was reliable in total dose computation. Our current institutional practice of point-based planning in ICBT resulted in significant number of patients’ OARs doses exceeded the volume constraint, because the total dose concept was not used propectively in planning.